First report of sour rot on tomato caused by Galactomyces reessii in Thailand - Nakarin Suwannarach (2018)
© 2016, The Phytopathological Society of Japan and Springer Japan. In May 2014, sour rot, an important postharvest disease of tomato, was found on tomato fruit (Solanum lycopersicum var. Roma) in Chiang Mai Province, Thailand. The causal yeast was isolated from lesions and identified as Galactomyces reessii based on morphological, biochemical and physiological characteristics and confirmed using comparisons of DNA sequences of D1/D2 domains of the large subunit ribosomal DNA. The isolated yeast caused rot symptoms on inoculated tomato fruits similar to natural symptoms in the field. This is the first report of tomato sour rot caused by G. reessii.